ESVS Volodos Lecture: Innovations and the Hippocratic Oath. (May 2018) - Gloviczki, Peter
Abstract : This lecture remembers Professor Nicolai Volodos, a pioneer innovator and a giant in vascular and endovascular surgery, who performed the first endovascular repair of a thoracic aneurysm in 1987 and developed a complex endovascular program by the end of the 1980s. The manuscript recalls major innovations and innovators in vascular surgery, examines the challenges innovators and those who adopt innovations face and discusses the modern meaning of the Hippocratic Oath. The author concludes that surgical innovations are essential to advance cost-effective care, and shared decision making on adopting new therapies by an ethical surgeon and a well informed patient is the cornerstone of ethical patient care.